2015
DOI: 10.1097/opx.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Keratoconus

Abstract: Keratoconus (KC) has been traditionally classified as a noninflammatory disease. Barring loss of function, the other classic signs of inflammation (heat, redness, swelling, pain) are not usually obvious or even apparent in KC. This clinical perspective examines the evidence and implications of numerous inflammatory processes that have been recognized in the tears of KC patients as well as some inflammation relevant differences found in the KC cornea. The roles of inflammation in corneal trauma attributed to ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 56 publications
(104 reference statements)
2
65
0
1
Order By: Relevance
“…It is possible that these findings correspond to epiphenomena, a possibility already suggested by Lema et al 22 As suggested by McMonnies, 25 should a new category of diseases be established: quasi-inflammatory or inflammatory-related conditions?…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…It is possible that these findings correspond to epiphenomena, a possibility already suggested by Lema et al 22 As suggested by McMonnies, 25 should a new category of diseases be established: quasi-inflammatory or inflammatory-related conditions?…”
Section: Resultsmentioning
confidence: 96%
“…As Mcmonnies 25 recently highlighted, another argument supporting the role of proinflammatory chemokines in corneal thinning is that in ocular rosacea several cases of pseudo-keratoconus have been reported. 121,122 Afonso et al 123 found higher concentration of IL-1 α and greater activity of MMP-9 in the tear fluid of patients with ocular rosacea than in control subjects.…”
Section: Corneal Stroma Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…A family history of ocular manifestations of atopy or seasonal allergies may have more significance. 24 22 However, atopy may have other implications for the etiology of KC.…”
Section: Atopymentioning
confidence: 99%